28- تعظيم استفادة جمهورية مصر العربية من عضوية تجمع البريكس في ضوء أولويات الرئاسة الهندية 2026 - خالد عطية; سحر البهائي (معهد التخطيط القومي, 2026)
تؤكد ورقة السياسات أن انضمام مصر إلى تجمع البريكس يمثل فرصة استراتيجية لإعادة تموضع الاقتصاد الوطني من خلال تنويع مصادر التمويل، وتعزيز الروابط التجارية، وتيسير نقل التكنولوجيا، وتوسيع آفاق التعاون جنوب–جنوب؛ غير أن تحقيق عوائد اقتصادية ملموسة يظل مشروطًا بقدرة الدولة على رفع كفاءة منظومتها المؤسسية، والانتقال من منطق التنسيق الإجرائي إلى نهج الإدارة الاستراتيجية القائمة على البرامج والنتائج القابلة للقياس. وفي ضوء أولويات الرئاسة الهندية لعام 2026، تحدد الورقة خمسة محاور تنفيذية رئيسية تشمل التمويل التنموي، والتصنيع المشترك ونقل التكنولوجيا، والتجارة وسلاسل القيمة، والتحول الرقمي والابتكار، والطاقة المستدامة، مع إبراز عدد من التحديات الهيكلية، في مقدمتها ضعف التنسيق المؤسسي، ومحدودية الاستفادة من أدوات التمويل المتاحة، واستمرار اختلال الميزان التجاري مع دول البريكس. وتخلص الورقة إلى أن تعظيم العائد التنموي من عضوية البريكس يتطلب تنفيذ إصلاحات مؤسسية عاجلة، وإعداد حافظة مشروعات قابلة للتمويل، وتفعيل أطر فعالة للمتابعة والتقييم، بما يضمن تحويل هذه العضوية إلى نتائج اقتصادية وتنموية ملموسة ومستدامة. The policy paper argues that Egypt’s accession to the BRICS grouping constitutes a strategic opportunity to reposition its national economy through the diversification of financing sources, the strengthening of trade linkages, the facilitation of technology transfer, and the expansion of South–South cooperation; however, the realization of tangible economic gains remains conditional upon enhancing institutional efficiency and transitioning from procedural coordination to a strategic management approach grounded in programmatic implementation and measurable results. Against the backdrop of the Indian Presidency’s 2026 priorities, the paper identifies five core implementation pillars: development finance, joint industrialization and technology transfer, trade and value chains, digital transformation and innovation, and sustainable energy, while also highlighting structural constraints, notably weak institutional coordination, underutilization of available financing instruments, and persistent trade imbalances with BRICS economies. The paper concludes that maximizing the developmental returns from BRICS membership necessitates urgent institutional reform, the establishment of a pipeline of bankable projects, and the operationalization of robust monitoring and evaluation frameworks to ensure the effective translation of membership into tangible and sustainable economic outcomes.